Serotonin transporter-deficient mice display enhanced adipose tissue inflammation after chronic high-fat diet feeding - Hoch, Johannes; Burkhard, Niklas; Zhang, Shanshan; Rieder, Marina; Marchini, Timoteo; Geest, Vincent; Krauel, Krystin; Zahn, Timm; Schommer, Nicolas; Hamad, Muataz Ali; Bauer, Carolina; Gauchel, Nadine; et al. (Frontiers in Immunology, 2023)
Introduction Serotonin is involved in leukocyte recruitment during inflammation. Deficiency of the serotonin transporter (SERT) is associated with metabolic changes in humans and mice. A possible link and interaction between the inflammatory effects of serotonin and metabolic derangements in SERT-deficient mice has not been investigated so far. Methods SERT-deficient (Sert-/-) and wild type (WT) mice were fed a high-fat diet, starting at 8 weeks of age. Metabolic phenotyping (metabolic caging, glucose and insulin tolerance testing, body and organ weight measurements, qPCR, histology) and assessment of adipose tissue inflammation (flow cytometry, histology, qPCR) were carried out at the end of the 19-week high-fat diet feeding period. In parallel, Sert-/- and WT mice received a control diet and were analyzed either at the time point equivalent to high-fat diet feeding or as early as 8-11 weeks of age for baseline characterization. Results After 19 weeks of high-fat diet, Sert-/- and WT mice displayed similar whole-body and fat pad weights despite increased relative weight gain due to lower starting body weight in Sert-/-. In obese Sert-/- animals insulin resistance and liver steatosis were enhanced as compared to WT animals. Leukocyte accumulation and mRNA expression of cytokine signaling mediators were increased in epididymal adipose tissue of obese Sert-/- mice. These effects were associated with higher adipose tissue mRNA expression of the chemokine monocyte chemoattractant protein 1 and presence of monocytosis in blood with an increased proportion of pro-inflammatory Ly6C+ monocytes. By contrast, Sert-/- mice fed a control diet did not display adipose tissue inflammation. Discussion Our observations suggest that SERT deficiency in mice is associated with inflammatory processes that manifest as increased adipose tissue inflammation upon chronic high-fat diet feeding due to enhanced leukocyte recruitment.